Variety of Candida in Women with Abnormal Vaginal Discharge - Guevara Duncan, José (2000)
OBJECTIVES: Vaginal discharge and related aymptoms are frequent complaints among young women. The aim of this study was to describe Candida species isolated from vaginal discharge samples, as well as the relationship between Candida species and some of these symptoms. MATERIAL AND METHODS: A survey of consecutive patients presenting with vaginal discharge in the course of normal consultations was conducted at the Hospital Loayza. One hundred women with vaginal discharge were surveyed, with main outcome measures being clinical evaluation, microbiological assessment of vaginal swabs (including fresh samples, stainings, cultures and fermentation tests). RESULTS: Candida species were isolated from 24 samples. 12 of them were identified as C. albicans, 6 C. tropicalis, 4 C. famata, 1 C. glabrata and 1 C. kruseii. No differences were found between clinical presentation of Candida vulvovaginitis caused by different Candida species. CONCLUSIONS: Features of vaginal discharge are unspecific for the specie. C. albicans is the commonest isolated specie causing vulvovaginitis. Serum culture is a quickly and accurate method to diagnose Candida species. When Candida species exist alone as pathogens, they are associated to Doderlein bacillus. The most frequent coexistent microorganism was Gardnerella vaginalis.